The Etnomatematika dalam Kesenian Jathilan: Analisis Unsur Geometri dan Pola Gerak - Juwairiyah Miftakhul Jannah; Nurul Arfinanti (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
This research aims to identify and describe the geometric elements and mathematical patterns contained in Jathilan traditional art. The research method used is qualitative ethnography through interviews with village residents who are also artists, village elders and village officials. The results of the research show that geometric elements appear in the shape of the lumping horse's properties, the arrangement of the dancers' formations, accompaniment and movement. The mathematical values ​​that emerge include the concepts of lines, circles, and repeating patterns. This study strengthens the view that mathematics is not only present in formal contexts, but also lives and develops in society's culture.